The c-Rel-c-Myc axis controls metabolism and proliferation of human T leukemia cells. (September 2020) - Li, Xinyuan; Luo, George; Li, Ting; Sun, Honghong; Wang, Wei; Eiler, Emily; Goldsmith, Jason R.; Chen, Youhai H.
Highlights: REL knockout lymphoma cells exhibited significant defects in cell growth and mitochondrial respiration. T cells lacking c-Rel had selective defects in the expression of inflammatory and metabolic genes including c-Myc. Expressing c-Myc in c-Rel-deficient lymphoma cells rescued their proliferative and metabolic defects. The human c-Rel-c-Myc axis controls lymphoma growth and metabolism and could be a therapeutic target for lymphomas. Abstract: Genome-wide association studies have established that human REL is a susceptibility gene for lymphoid cancers and inflammatory diseases. REL is the hematopoietic member of the nuclear factor-κB (NF-κB) family and is frequently amplified in human lymphomas. However, the mechanism through which REL and its encoded protein c-Rel affect human lymphoma is largely unknown. Using both loss-of-function and gain-of-function approaches, we studied the roles of REL gene in human Jurkat leukemia cells. Compared with control Jurkat cells, REL knockout cells exhibited significant defects in cell growth and mitochondrial respiration. Genome-wide transcriptome analyses revealed that T cells lacking c-Rel had selective defects in the expression of inflammatory and metabolic genes including c-Myc. We found that c-Rel controlled the expression of c-Myc through its promotor, and expressing c-Myc in c-Rel-deficient lymphoma cells rescued their proliferative and metabolic defects. Thus, the human c-Rel-c-Myc axis controls lymphoma growth and metabolism and could be a therapeutic target for lymphomas.